Pengaruh Pendapatan Kontribusi, Klaim, Dan Hasil Investasi Terhadap Pertumbuhan Aset Perusahaan Pt Asuransi Allianz Life Unit Syariah - Jajuli, Jajuli; Monica Sari (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
The need for insurance services is increasingly felt by both individuals and businesses in Indonesia. Insurance is a financial means in managing household life both in the face of basic risks such as the risk of death or the risk of property owned. Research Problem Formulation: 1) How does the contribution affect the assets of PT Asuransi Allianz Life Indonesia Sharia Unit in 2014 – 2020? 2) How does the claim affect the assets of the company PT Asuransi Allianz Life Indonesia Sharia Unit in 2014 – 2020? 3) How does the investment return affect the assets of the PT Asuransi Allianz Life Indonesia Sharia Unit in 2014 – 2020? 4) How do Contributions, Claims, and Investment Returns simultaneously affect the Growth of Company Assets at PT Asuransi Allianz Life Indonesia Sharia Unit in 2014 – 2020?. The objectives of this study are: 1) To determine the effect of Contribution opinion on Company Assets of PT Asuransi Allianz Life Indonesia Sharia Unit in 2014 – 2020. 2) To determine the effect of Claims on Company Assets of PT Asuransi Allianz Life Indonesia Sharia Unit in 2014 – 2020. 3) To determine the effect of Investment Return on Company Assets of PT Asuransi Allianz Life Indonesia Sharia Unit in 2014 – 2020.4) To simultaneously determine the effect of Contribution, Claim, and Investment Return on Asset Growth of PT Asuransi Allianz Life Indonesia Sharia Unit in 2014 – 2020. The method used used in this research is quantitative research method, with descriptive analysis. This descriptive study is intended to provide an overview and explain the state of the company which is illustrated through the Financial Statements and Annual Reports. The results of this study are: 1) The results of hypothesis testing of contribution variables have a significant effect on assets. This can be seen from the t-test or partial test performed, the results of the study indicate that the value of t > t (2.058 > 1.708) thus H1 is accepted or it can be concluded that the independent variable partially has a significant effect on the dependent variable. 2) The results of hypothesis testing claim variables have a significant effect on assets. This can be seen from the t-test or partial test conducted, the results of the study indicate that the value of t > t (5.030 > 1.708) thus H2 is accepted or it can be concluded that the independent variable partially has a significant effect on the dependent variable. 3) The results of the hypothesis testing of the Investment Return variable have a significant effect on assets. This can be seen from the t-test or partial test performed, the results of the study indicate that the value of t > t (3.453 > 1.708) thus H3 is accepted or it can be concluded that the independent variable partially has a significant effect on the dependent variable. 4) The results of hypothesis testing Contribution, Claim, and Investment Return variables have a significant effect on Assets. This can be seen from the f-test or simultaneous test, the results show that the value of f > f (8.519 > 2.760) thus H4 is accepted or it can be concluded that the independent variables together have a significant effect on the dependent variable.